The text is dead: long life to the texts. Textual pluralism and digital editions (Prassi Ecdotiche della Modernità Letteraria, 2018)
This article questions the relationship between digital technology and the emergence of a renewed interest in the text as transmitted by documents and the consequent increase in the production of diplomatic editions. From an analysis of the multifaceted textuality of the medieval period, the article moves on to review the social, economic and cultural motivations that led to the elaboration of the idea of the Only Text, an idea that is now challenged by the advent of the digital.
Keywords: digital humanities; digital philology; digital edition; diplomatic edition